Sinergi Edukasi Fikih Ramadhan dan Aksi Sosial: Pendampingan Keislaman di MWCNU Paiton - Bashori, Bashori Alwi; Musthafa, Musthafa Syukur; Rakib, Abdur Rakib (Yayasan Literasi Altruis Khatulistiwa, 2025)
The Paiton community faces two main problems during Ramadan: a low understanding of the fiqh of fasting and weak social concern for orphans and poor families. Many people perform religious practices based on tradition without a strong fiqh foundation, leading to potential mistakes in fasting, zakat fitrah, and other worship. Vulnerable groups often face economic hardship that affects the quality of their worship and daily life. To address these issues, a community service program was implemented using educational and social approaches, including interactive Ramadan fiqh studies and the provision of aid and spiritual support for orphans and the poor. The program was carried out in three stages: planning through coordination and needs assessment; implementation through studies and social activities; and participatory evaluation with the community. The results show improved understanding of fiqh and growing social solidarity. This program offers a practical solution to religious and social challenges and strengthens collaboration between academics, religious scholars, and the local community.